PENGARUH UKURAN PERUSAHAAN DAN LIABILITAS TERHADAP LABA BERSIH PADA PERUSAHAAN FOOD AND BAVERAGE TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2020-2024 - Maziyatul Imani; Asfufi Nanang; Setyawardhana Nugraha (Accounting Journal of Ibrahimy (AJI), 2026)
Companies that developed and grew rapidly influenced the economic condition of the country because they gained profits from the sales of their products. However, since the implementation of the global market, business competition, especially in Indonesia, became increasingly tight. This condition demanded business actors to improve their capabilities and formulate strategies so as not to lag behind other companies and not to lose in business competition, especially with similar businesses. The income statement information served as the basis for decision-making for creditors to provide loans to companies. This study aimed to examine the effect of firm size and liabilities on net income in food and beverage companies listed on the IDX in 2020–2024. The method used in this study was causal associative with a quantitative approach. The data used in this study were secondary data obtained through the official website www.idx.co.id in the form of annual financial reports of food and beverage companies for 2020–2024. The sample of this study was taken using a purposive sampling method. This study used 20 companies as samples that met the criteria. The data analysis method used in this study was quantitative data analysis with Microsoft Excel and multiple linear regression, hypothesis testing, and classical assumption testing with the help of IBM SPSS 25 software. The results of this study revealed that firm size measured by total assets had a positive and significant effect on net income. Liabilities had a positive and significant effect on net income. Simultaneously, firm size and liabilities had a significant effect on net income of food and beverage companies listed on the IDX in 2020-2024.